Reproductive biology of dendropsophus haddadi (Bastos and pombal, 1994), a small treefrog of the atlantic forest - Silva, Nelson R.; Neto, José A.; Prado, Cynthia P. A. [UNESP]; Mott, Tamí (My University, 2019)
Terrestrial reproduction has evolved at least 48 times in the evolutionary history of anurans. Most species in the genus Dendropsophus deposit eggs in water, but some, including Dendropsophus haddadi, lay terrestrial eggs. This species is restricted to the Atlantic forest in Brazil and herein, we describe its reproductive biology. Individuals were observed at a height of 3-5 meters on vegetation at the edge of temporary ponds. Males are territorial, emitted calls, visual signals, and engaged in physical combats. Clutches were found at the margins of temporary ponds on trunks, leaves and branches. The number of hatchlings correlated with clutch size and our observations suggest that females may protect the eggs against desiccation following oviposition in the absence of rain. This form of parental care is a novelty for the genus and future studies should detail and assess costs and benefits of this behaviour. The Atlantic forest harbours an extremely rich frog diversity, however information on species natural history is scarce, which may hamper studies on behavioural evolution, phylogeny, as well as conservation actions and decisions.
Keywords: Anura; Courtship; Eggs; Embryo development; Territoriality